A development of prototype web based template teaching aid system / Harizan Zuria Zakaria - Zakaria, Harizan Zuria (2005)
One of the major problems with subject notes given by lecturers is that it is not standardized with other lecturer's notes even for the one particular same subject. Standardization of notes is necessary to make teaching and learning process more efficient and beside that it's a benefit for the lecturers and the students. This research is focusing on development of prototype Web Based Template Teaching Aid System that allows the lecturers to edit and write notes in the same styles and also acts as a distribution center of notes. The objectives of this project are to design and develop template that will enable lecturer's notes to be standardized and to design the interface of the prototype. To choose or identify the best slide layout design that being used in this prototype, researcher had made an analysis to many slide layout design samples. Through this development, this web based system provides one platform to user in order to manage notes in a simple way and information can be shared and spread via the Internet.